Dermatoses provocadas por animais venenosos - Haddad Júnior, Vidal [UNESP]; Cardoso, João Luiz Costa (My University, 1999)
The venomous brazilian animals can cause accidents in human beings with great frequency. By means of this revision, the authors talk about the species and the accidentes more commons and more serious in our country. The function of the dermatologist in diagnostic, treatment and prevention of the accidents is enphatized.
Dermatoses caused by poisonous animals
Keywords: Animals; Poisonous; Poisons; Venoms; poison; venom; animal; aquatic fauna; arachnid; Brazil; coleoptera; invertebrate; nonhuman; review; scorpion; skin disease; vertebrate